2016
DOI: 10.1159/000453193
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glutathione Synthesis Induced by Exhaustive Running Exercise via the Decreased Influx Rate of L-Cysteine in Rat Erythrocytes

Abstract: Background/Aims: The main purpose of this study was to investigate the effect of exhaustive exercise on L-cysteine uptake and its effect on erythrocyte glutathione (GSH) synthesis and metabolism. Methods: Rats were divided into three groups: sedentary control (C), exhaustive running exercise (ERE) and moderate running exercise (MRE) (n=12 rats/group). We determined the L-cysteine efflux and influx in vitro in rat erythrocytes and its relationship with GSH synthesis. Total anti-oxidant potential of plasma was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The activities of the antioxidant enzymes superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) in CD4 + T cells were measured by colorimetric analysis [ 20 ]. GSH-Px activity was detected using the DTNB method [ 21 ], CAT activity was measured using the ammonium molybdate method [ 22 ], and SOD activity was measured using the xanthine-oxidase method [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The activities of the antioxidant enzymes superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) in CD4 + T cells were measured by colorimetric analysis [ 20 ]. GSH-Px activity was detected using the DTNB method [ 21 ], CAT activity was measured using the ammonium molybdate method [ 22 ], and SOD activity was measured using the xanthine-oxidase method [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Glutathione (GSH) is an important redox active biomolecule critical in maintaining cellular and organism homeostasis [4,5]. Previous studies suggested that abnormal metabolism of GSH was closely related with various pathological and physiological conditions [6,7]. Whillier et al showed that the glutathione synthesis rate significantly decreased in stored RBCs after 6 weeks [8].…”
Section: Introductionmentioning
confidence: 99%
“…Similar oxidative effects of extreme exercise that induce RBC membrane lipid oxidation were also reported. 32 In exhausted animals, the free radicals produced from the ATP-generating system (which include O2 •− and H2O2, respectively) enhanced exercise-related oxidative stress. 33 These free radicals which are dismasted by SOD, an antioxidant defense against hydrogen peroxide could be finally wear off by glutathione peroxidase.…”
Section: Discussionmentioning
confidence: 99%